Analisis Risiko (K3) Metode Hazard Identification Risk Assesment And Risk Control (HIRARC) di Departemen Laboratorium PT. ABC - Moh. Fikri Pratama; Elly Ismiyah; Akhmad Wasiur Rizqi (Universitas Nasional, 2022)
PT. ABC is a company that produces cooking oil and margarine whose products are well known throughout Indonesia, located in the city of Gresik, East Java. The main basic ingredient in manufacture of cooking oil and margarine is CPO (crude palm oil) which will be proceed at refinery and fraction stages. During the production process, quality control is carried out in order to get maximum results from raw to finished goods in Laboratory. In laboratory department, work accidents often occur, whether are low, medium or very hight. There are many potential hazards and risks due to direct contact with chemicals such as HCL, H2SO4 and Ammonium. To overcome this, a study was conducted using the HIRARC (Hazard Identification Risk Assessment And Risk Control) and based on (OHSAS) Occupational Health and Safety Assessment Series 18001:2007. The results of the HIRARC method show there are two extreme risk levels, two high levels, two low levels, and three medium levels. Controlling risks are in the form of eliminating and substituting points relevant to laboratory condition.